Computers in a GLP environment - McNamee, John (Henry Stewart Talks, 2012)
History of computers in GLP, Improvements brought about in efficiency and accuracy in data collection and reporting, The reasons for using computers in GLP, The most important aspects of computer systems design and operation with regards to GLP